Xanthan gum-assisted fabrication of stable emulsion-based oleogel structured with gelatin and proanthocyanidins. (June 2021) - Pan, Haibo; Xu, Xinlei; Qian, Ziqi; Cheng, Huan; Shen, Xuemin; Chen, Shiguo; Ye, Xingqian
Abstract: Oleogelation based on emulsion using food-approved biopolymers is a feasible strategy to substitute solid fat with harmful trans and saturated fatty acids, providing food products with a better nutritional profile. However, oil with high content of unsaturated fatty acids is prone to oxidation, resulting in quality loss of food products. In the present study, proanthocyanidins from Chinese bayberry leaves (BLPs) were incorporated into emulsion-based oleogel to remedy the defect through the formation of colloidal complexes with gelatin. Oleogel stabilized with the colloidal complexes showed higher stability with lower oil loss and higher gel strength, compared to that with gelatin only. Then different polysaccharides were applied to further promote oleogel stability. However, polysaccharides abrogated the promotive effect of BLPs and resulted in comparable stability of oleogels with BLPs or not, which was confirmed with cryo-SEM observation. Then the application of oleogel with BLPs as margarine alternative was verified with batter properties, quality loss of cakes and oil stability in cakes. Batter properties of oleogel with BLPs were comparable to that without BLPs, and more close to margarine than oil. For quality loss, textural properties of oleogel cakes with BLPs or not resembled each other and were significantly better than oil cakes in hardness and chewiness and margarine cakes in cohesiveness. Particularly, BLPs were verified to retard oil oxidation in both oleogel and cakes prepared with oleogel. Overall, incorporation of BLPs into oleogel was feasible to improve its oil stability and keep its application in cake products. Graphical abstract: Image 1 Highlights: Proanthocyanidins were incorporated into emulsion-based oleogel. Xanthan gum improved the gel strength of oleogel with proanthocyanidins. Proanthocyanidins didn't influence the functionality of oleogel in cakes. Proanthocyanidins improved oil oxidation stability in oleogel and cakes. The oleogel was an alternative to margarine for preparing cake with good quality.